DINAMIKA DAN PENGARUH UTANG LUAR NEGERI DAN PMA TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 1995-2024 - Suirlan, Rita SUIRLAN, (Politeknik Bisnis Indonesia, 2025)
Abstract This study aims to analyze the dynamics and influence of foreign debt and foreign investment (FDI) on economic growth in Indonesia. Foreign debt and FDI are two important components in development financing that can have positive or negative impacts depending on their management. Using time series data and multiple linear regression analysis methods, this study analyzes the long-term relationship between the two independent variables on GDP as an indicator of economic growth. The results of the analysis show that foreign debt has a positive and significant influence on GDP, but in the long term it can pose a risk of fiscal dependency. Meanwhile, FDI has a positive and insignificant influence on GDP through increased investment and labor absorption. These findings provide important implications for the formulation of macroeconomic policies, especially in managing foreign financing sustainably and effectively to encourage inclusive GDP. Keywords: Foreign Debt, Foreign Investment, GDP